Blood signatures for second stage human African trypanosomiasis: a transcriptomic approach - Julius Mulindwa; Enock Matovu; John Enyaru; Christine Clayton (BMC, 2020)
Abstract Background Rhodesiense sleeping sickness is caused by infection with T. b rhodesiense parasites resulting in an acute disease that is fatal if not treated in time. The aim of this study was to understand the global impact of active T. b rhodesiense infection on the patient's immune response in the early and late stages of the disease. Methods RNASeq was carried out on blood and cerebral spinal fluid (CSF) samples obtained from T. b. rhodesiense infected patients. The control samples used were from healthy individuals in the same foci. The Illumina sequenced reads were analysed using the Tuxedo suite pipeline (Tophat, Cufflinks, Cuffmerge, Cuffdiff) and differential expression analysis carried out using the R package DESeq2. The gene enrichment and function annotation analysis were done using the ToppCluster, DAVID and InnateDB algorithms. Results We previously described the transcriptomes of T. b rhodesiense from infected early stage blood (n = 3) and late stage CSF (n = 3) samples from Eastern Uganda. We here identify human transcripts that were differentially expressed (padj < 0.05) in the early stage blood versus healthy controls (n = 3) and early stage blood versus late stage CSF. Differential expression in infected blood showed an enrichment of innate immune response genes whereas that of the CSF showed enrichment for anti-inflammatory and neuro-degeneration signalling pathways. We also identified genes (C1QC, MARCO, IGHD3-10) that were up-regulated (log2 FC > 2.5) in both the blood and CSF. Conclusion The data yields insights into the host's response to T. b rhodesiense parasites in the blood and central nervous system. We identified key pathways and signalling molecules for the predominant innate immune response in the early stage infection; and anti-inflammatory and neuro-degeneration pathways associated with sleep disorders in second stage infection. We further identified potential blood biomarkers that can be used for diagnosis of late stage disease without the need for lumbar puncture.